PENERAPAN METODE RESISTIVITAS KONFIGURASI SCHLUMBERGER UNTUK MENDETEKSI PERSEBARAN AIR LINDI (STUDI KASUS TPA TERJUN MARELAN) - Harahap, Afniar; Sirait, Ratni; Lubis, Lailatul Husna (JOURNAL ONLINE OF PHYSICS, 2023)
Leachate has the potential to be used as organic fertilizer because it contains high levels of minerals and organic matter. In the leachate there are several compounds, namely heavy metal compounds, salts, nitrogen compounds and various types of other organic matter. Leachate leachate also contains very fine suspended matter from the decomposition of microbes, usually consisting of Ca, Mg, Na, K, Fe, Chloride, Sulfate, Phosphate, Zn, Ni, CO2, H2O, N2, NH3, H2S, Organic acids , and H2. This study aims to find out how the subsurface layer in the Medan Marelan Falls Landfill area, the distribution of leachate in the Medan Marelan Falls Landfill. 1D resistivity measurements were only carried out in the Medan Marelan Falls TPA area. The geophysical method used in this study is the Schlumberger configuration. This research was conducted at three points along the 200 meter track. on line I is at a depth of 6.92 m with a resistivity value of 3.16 Î©m with a North to South flow direction. On track II it is at a depth of 1.15 m, 4.53 m, and 22.1 m with a resistivity value of 1.5 Î©m, 2.25 Î©m, and 5.05 Î©m respectively with the North to West flow direction. On track III it is at a depth of 1.19 m, 20.8 m, and 53.9 m with resistivity values of 1.54 Î©m, 3.51 Î©m, and 1.13 Î©m respectively with North to West flow direction. The distribution of leachate at the Medan Marelan Falls TPA which dominates is on track III marked with black to bluish color images.